KARAKTERISTIK PENERIMA VAKSIN BOOSTER COVID-19 DI KOTA SUNGAI PENUH - Marta Butar Butar; Ummi Kalsum; Hendra Dhermawan Sitanggang (LLDIKTI Wilayah X, 2023)
Coronavirus Disease 2019 (COVID-19) is still a pandemic today. Various coping strategies have been carried out both globally and nationally. Efforts are being made not only through prevention efforts through health protocols, but also through vaccination efforts. Therefore, this study aims to describe the acceptance of the COVID-19 booster vaccine in Sungai Penuh City, Jambi Province. This research is a descriptive study with a cross sectional research design. The population of this study were all people aged ≥18 years who live in Sungaipenuh City who had received the Covid-19 Booster Vaccine with a total sample of 68 people. Data were analyzed descriptively to determine the frequency distribution of each research variable. The results of the study showed that of the 68 respondents who received the Covid-19 booster vaccine, 63.2% were able to show vaccine certificates at the time of data collection in the field. Based on the reasons for wanting to be vaccinated, 70.6% of respondents said they wanted immunity and 45.6% of respondents said they wanted to be safe against a pandemic